2014 Seventh International Symposium on Computational Intelligence and Design 2014
DOI: 10.1109/iscid.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

Application of Web Data Mining Technique to Enterprise Management of Electronic Commerce

Abstract: As an absolutely necessary to electronic commerce management, with the methods of path analysis, correlation analysis, analysis of sequence pattern, assortment Analysis, cluster Analysis, knowledge discovery category, Web data mining technique offers strong support of data analysis technique by extracting information from mass data of electronic commerce to enterprises. By following certain Web data mining procedures in electronic commerce management, and according to date sources by keeping to themes of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…The paper [17] presents the application of the web data mining technique for enterprise management in e-commerce. It is an important issue for all scientific disciplines.…”
Section: Knowledge Discovery From a Classification Viewpointmentioning
confidence: 99%
“…The paper [17] presents the application of the web data mining technique for enterprise management in e-commerce. It is an important issue for all scientific disciplines.…”
Section: Knowledge Discovery From a Classification Viewpointmentioning
confidence: 99%
“…In 2014, Chen [28] suggested that the by following certain Web information mining methodology in electronic business administration, and as indicated by date sources by keeping to subjects of electronic trade administration, doing web date in preprocessing, change, joining, learning disclosure and mode examination, endeavors can guarantee the security of system data framework, enhance effectiveness of client relationship administration, improve electronic business site development and develop arrange activity administration framework to give choice help to electronic business and empower the ventures to be with sound intensity in the pattern of electronic business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in Wu and Liu (2009), a system for diagnosing damage to internal combustion engines using wavelet packet transformation (WPT) and artificial neural network (ANN) techniques has been proposed (Staszewski et al 1997;Specht 1991). Currently, most of the research focuses on data mining algorithms, although other stages are equally important for the successful implementation of the whole process (Correia et al 2003;Jayamalini and Ponnavaikko 2017;Chen 2015;Linoff and Berry 2011). There are many different descriptions in the literature of both individual steps and entire design and decision support processes (Pijls and Bruin 2001;Horzyk 2012).…”
Section: Introductionmentioning
confidence: 99%